Biohydrogen Production from Acid Pre-treated Grass - Halim, Amirul Ridzuan; Seswoya, Roslinda (Recent Trends in Civil Engineering and Built Environment, 2024)
Hydrogen is an ideal energy resource. It is an attractive alternative energy source since it generates a huge amount of energy with only water as a reaction product. Biohydrogen is gaining popularity among renewable energy sources due of its high energy conversion to usable power and low pollution production. Grass waste has been identified as a suitable substrate among biomass residues for biohydrogen production. In this study, HCl acid was used to pretreat grass waste. Pretreatment process was applied to enhance hydrogen fermentation of grass waste. This study aims to gain the knowledge on how acid pre-treated grass (4% HCl) feasible for dark fermentation. Automatic Methane Potential Test System (AMPTS II) was used for Biochemical Hydrogen Potential (BHP) test. Biochemical Hydrogen Potential (BHP) test was used to determine the hydrogen yield from acid pre-treated grass (4% HCl). The hydrogen production potential and the hydrogen production from acid pre-treated grass (4% HCl), were 46.62 ml H2/ g VS and 180.9 mL respectively. The Modified Gompertz Modelling was not appropriate for assessing the kinetic of hydrogen production from acid pre-treatead grass (4% HCl), due to the difference between laboratory data and Modified Gompertz Model which was exceeded 50%. Keywords: Biohydrogen, Grass Waste, Acid Pretreatment